Heatwave‐induced synchrony within forage fish portfolio disrupts energy flow to top pelagic predators. (6th March 2021) - Arimitsu, Mayumi L.; Piatt, John F.; Hatch, Scott; Suryan, Robert M.; Batten, Sonia; Bishop, Mary Anne; Campbell, Rob W.; Coletti, Heather; Cushing, Dan; Gorman, Kristen; Hopcroft, Russell R.; Kuletz, Kathy J.; et al.
Abstract: During the Pacific marine heatwave of 2014–2016, abundance and quality of several key forage fish species in the Gulf of Alaska were simultaneously reduced throughout the system. Capelin ( Mallotus catervarius ), sand lance ( Ammodytes personatus ), and herring ( Clupea pallasii ) populations were at historically low levels, and within this community abrupt declines in portfolio effects identify trophic instability at the onset of the heatwave. Although compensatory changes in age structure, size, growth or energy content of forage fish were observed to varying degrees among all these forage fish, none were able to fully mitigate adverse impacts of the heatwave, which likely included both top‐down and bottom‐up forcing. Notably, changes to the demographic structure of forage fish suggested size‐selective removals typical of top‐down regulation. At the same time, changes in zooplankton communities may have driven bottom‐up regulation as copepod community structure shifted toward smaller, warm water species, and euphausiid biomass was reduced owing to the loss of cold‐water species. Mediated by these impacts on the forage fish community, an unprecedented disruption of the normal pelagic food web was signaled by higher trophic level disruptions during 2015–2016, when seabirds, marine mammals, and groundfish experienced shifts in distribution, mass mortalities, and reproductive failures. Unlike decadal‐scale variability underlying ecosystem regime shifts, the heatwave appeared to temporarily overwhelm the ability of the forage fish community to buffer against changes imposed by warm water anomalies, thereby eliminating any ecological advantages that may have accrued from having a suite of coexisting forage species with differing life‐history compensations. Abstract : The Pacific marine heatwave was a prolonged warming event that led to reduced abundance and quality of small pelagic forage fishes. This caused a major disruption in the pelagic marine food web that precipitated large‐scale mortality and reproductive failures in upper trophic level predators. Unlike decadal‐scale variability underlying ecosystem regime shifts, the heatwave appeared to temporarily overwhelm the ability of the middle trophic level to buffer against changes imposed by warm water anomalies.